Processamento auditivo em escolares: um estudo longitudinal - Costamilan, Cintia Maria (2004)
This study aimed to perform a longitudinal study of the auditory processing in a group of children with and without learning difficulties complaints, using the SSW test, portuguese version (Borges, 1986). Two groups of children from a public school in Santa Maria were studied, being divided in 25 children without learning difficulties complaints (A group) and 13 children with complaints (B group). All children were submitted to anamnesis, otorhinolaryngologic exam, basic audiologic evaluation and auditory processing evaluation. The following SSW Test variables were examined: competitive right (CR), competitive left (CL ) and amount of errors ( AE ). The evaluations ocurred in two phases with two years interval between them as the study was a longitudinal one. The results found showed that for the two studied groups there was no difference between male and female genders, in the SSW variable studied; the B group showed response statistically inferior in relation to A group in the two evaluation phases; the CL condition always showed a greater number of errors when compared to the CR condition in both groups and evaluations; it was possible to confirm statistically a response improvement related to time for the two groups of children, becoming evident the maturation factor influence and it was not observed statistitically significant difference between the groups A and B concerned to evolution related to time, that is, both groups had an improvement, with none of the two groups being better than the other . After this research and considering the experimental condition used, it was possible to conclude that the auditory processing in children with learning difficulties complaints was statistically inferior to children with no complaints in the two moments of the SSW Test, however, there was similar improvement in both groups related to time.